Encyclopedia of Polymer Science and Technology 2016
DOI: 10.1002/0471440264.pst256.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polycyanoacrylates

Abstract: Alkyl 2‐cyanoacrylate monomers are commonly used as instant adhesives or “superglue,” mainly because of their unique ability to undergo rapid polymerization under ambient conditions on a wide range of surfaces. This article overviews the chemistry and physical properties of these materials, the most common methods of preparation, their mode(s) of polymerization, and typical performance properties. The main performance limitations of alkyl 2‐cyanoacrylate adhesives, such as poor hot strength and resistance to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…Cyanoacrylate adhesives cure rapidly on skin surfaces (within 5–60 s). 6 The first generation of cyanoacrylate adhesives were based on lower alkyl (methyl) ester monomers and caused tissue toxicity. Research showed that the longer the hydrocarbon group at the –R position, the slower the rate of polymerization, the less heat released during polymerization, and the lower the histotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanoacrylate adhesives cure rapidly on skin surfaces (within 5–60 s). 6 The first generation of cyanoacrylate adhesives were based on lower alkyl (methyl) ester monomers and caused tissue toxicity. Research showed that the longer the hydrocarbon group at the –R position, the slower the rate of polymerization, the less heat released during polymerization, and the lower the histotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Alkyl 2-cyanoacrylates or cyanoacrylates (CAs) are a family of vinyl monomers renowned for their high reactivity, instant adhesive properties, and wide-ranging applications [1,2,3,4,5,6]. Short chain CAs, like methyl- and ethyl 2-cyanoacrylate have found great utility as the major components of industrial and household instant adhesives or “super glues”, including those manufactured at Henkel under the Loctite brand (Table 1) [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Short chain CAs, like methyl- and ethyl 2-cyanoacrylate have found great utility as the major components of industrial and household instant adhesives or “super glues”, including those manufactured at Henkel under the Loctite brand (Table 1) [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations